Skin senescence—from basic research to clinical practice - Dorf, Natalia; Maciejczyk, Mateusz (Frontiers in Medicine, 2024)
The most recognisable implications of tissue ageing manifest themselves on the skin. Skin laxity, roughness, pigmentation disorders, age spots, wrinkles, telangiectasia or hair greying are symptoms of physiological ageing. Development of the senescent phenotype depends on the interaction between ageing cells and remodelling of the skin's extracellular matrix (ECM) that contains collagen and elastic fibre. Ageing changes occur due to the combination of both endogenous (gene mutation, cellular metabolism or hormonal agents) and exogenous factors (ultraviolet light, environmental pollutants, and unsuitable diet). However, overproduction of mitochondrial reactive oxygen species (ROS) is a key factor driving cellular senescence. Ageing theories have disclosed a range of diverse molecular mechanisms that are associated with cellular senescence of the body. Theories best supported by evidence include protein glycation, oxidative stress, telomere shortening, cell cycle arrest, and a limited number of cell divisions. Accumulation of the ECM damage is suggested to be a key factor in skin ageing. Every cell indicates a functional and morphological change that may be used as a biomarker of senescence. Senescence-associated β-galactosidase (SA-β-gal), cell cycle inhibitors (p16INK4a, p21CIP1, p27, p53), DNA segments with chromatin alterations reinforcing senescence (DNA-SCARS), senescence-associated heterochromatin foci (SAHF), shortening of telomeres or downregulation of lamina B1 constitute just an example of ageing biomarkers known so far. Ageing may also be assessed non-invasively through measuring the skin fluorescence of advanced glycation end-products (AGEs). This review summarises the recent knowledge on the pathogenesis and clinical conditions of skin ageing as well as biomarkers of skin senescence.